PENGARUH MENGHAFAL AL-QUR’AN METODE ONE DAY ONE AYAT TERHADAP PENINGKATAN DAYA INGAT ANAK USIA 5-6 TAHUN DI TK MALIMPUNG PATAMPANUA PINRANG: Pengaruh Menghafal Al Qur'an Metode One Day One Ayat Terhadap Peningkatan Daya Ingat Anak Usia 5-6 Tahun - Paradiba Qisti Albab Idrus; Muhamammad Akil Musi; Muhammad Yusri Bachtiar (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
There are various ways to improve early childhood memory, one of which is by memorizing the Qur'an. There are so many methods of memorizing the Koran that were developed to make it easier to memorize the Koran, including in Indonesia itself there are various methods, one of which is the One Day One Verse Method. The One Day One Verse method itself was first introduced by Ustadz Yusuf Mansur as the founder of Darul Qur'an. This study aims to identify the effect of the One Day One Verse method on improving the memory of children aged 5-6 years in TK MALIMPUNG. This study uses a quantitative approach with experimental methods, and the type of experiment used is quasi-experimental with a nonequivalent control group design. The population in this study were all students of group B TK MALIMPUNG. The sampling of this research used random sampling technique. The sample of this study were 36 children, 18 children as the experimental group and 18 children as the control group. Data collection techniques were carried out by observation, test, and documentation techniques. The data analysis technique used is the help of IBM SPSS Statistics 22. The data analysis method used is the t-test. Based on the results of the significance level, the results obtained are 0.767> 0.05. Based on the results of the data analysis, it can be concluded that there is no effect of memorizing the Qur'an using the One Day One Verse Method on the Memory Improvement of children aged 5-6 years